Taxonomic significance of petiole anatomical characteristics of selected Hoya R.Br. (Apocynaceae) species in Malaysia - Noraini Talip,; Maryam Zulkarnain,; Syazwani Basir,; Mohamad Ruzi Abdul Rahman,; Hamidun Bunawan,; Nurnida Mohd Kamal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to identify the common characteristics, variations and diagnostics features of petiole anatomy that can be used to differentiate, identify and classify ten Hoya species. This anatomical study involves incision with a sliding microtome, staining with Safranin and Alcian green, hydration with a series of alcohols, slide preparation, drying process, and observation under a light microscope. The results of the study show that all species share five common characteristics: the presence of cuticles, the number of petiole epidermal cells, the presence of latex cells and ducts, and the presence of hypodermis layers. A total of nine anatomical variations of the petiole were observed, namely the outline shape of the petiole, the pattern of vascular tissue, the type of additional vascular bundles, the presence and pattern of sclerenchyma cells, the presence of sclereid and collenchyma cells, the presence and type of crystals, the presence of starch nodules, the presence and type of trichomes. Diagnostic features of the petiole anatomy of some study species can also be identified. The dichotomous key for identifying the studied Hoya species was constructed using the petiole anatomical features obtained from the study. In conclusion, the anatomical characteristics of Hoya leaves have taxonomic value and can provide added value for the differentiation and identification of Hoya species in Peninsular Malaysia.